1999
DOI: 10.1016/s0378-1097(99)00105-6
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the cytoplasmic protein tyrosine kinase activity of the Antarctic psychrotrophic bacterium Pseudomonas syringae

Abstract: The Antarctic psychrotrophic bacterium Pseudomonas syringae contains a 66-kDa cytoplasmic protein which was found to be phosphorylated on a tyrosine residue [Ray, M.K. et al. (1994) FEMS Microbiol. Lett. 122, pp. 49^54]. To investigate the nature of the cytoplasmic protein tyrosine kinase and its role in the bacterial physiology, we carried out some biochemical studies of the enzyme in vitro in the presence of exogenous peptide substrates and expression studies in vivo at low and high temperature during variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
1
1
0
Order By: Relevance
“…The phosphate is then transferred to aspartate component of the response regulator present in the cytoplasm, which contains a DNA binding domain and a transcription activation domain (Shivaji, 2007). A similar 66 kDa cytosolic protein which was found to be phosphorylated at its tyrosine residue, was reported much earlier and may also function as a response regulator (Jagtap and Ray, 1999). The response regulator in addition acts as a transcriptional regulator and performs the function of transcription initiation of various cold expressed genes.…”
Section: Responses In Bacteriasupporting
confidence: 55%
“…The phosphate is then transferred to aspartate component of the response regulator present in the cytoplasm, which contains a DNA binding domain and a transcription activation domain (Shivaji, 2007). A similar 66 kDa cytosolic protein which was found to be phosphorylated at its tyrosine residue, was reported much earlier and may also function as a response regulator (Jagtap and Ray, 1999). The response regulator in addition acts as a transcriptional regulator and performs the function of transcription initiation of various cold expressed genes.…”
Section: Responses In Bacteriasupporting
confidence: 55%
“…These 30 and 85 kDa proteins phosphorylate more at higher temperature (30°C), whereas the 65 kDa protein phosphorylates only between 15 and 0°C (Ray et al ., 1994a). A 66 kDa protein was identified as a cytoplasmic tyrosine kinase that is involved in temperature sensing (Jagtap and Ray, 1999). These results indicated that temperature‐dependent phosphorylation of LPS and membrane proteins play important roles in adaptation to and growth at low temperature in P. syringae (Fig.…”
Section: The P Syringae Lz4w Plasma Membranementioning
confidence: 99%